Power shift and administrative reforms - governments in transition. - Phang, Siew Nooi * (School of Business, Sunway University, 2011)
It is evident that administrative reforms are undertaken by many countries in the world today and in fact, administrative change appears to be a constant factor in regimes that desire to reform their social, political and economic systems. Normally, reform initiatives are regarded as necessary for organizations that want to adapt to the changing environment and to be able to expand and cope with increasing activities and global challenges. Nevertheless, strategies for reform initiatives will differ between sectors and also between nations as each country tries to handle reform in accordance with the country?s administrative traditions, political and cultural nuances and level of economic development. The process of reform may involve a particular sector or administration of the government or an entire level of the government such as the local government. The main characteristic of administrative reform is normally projected in attempts to decentralize powers and autonomy to lower levels of government. It connotes importance that such transition of powers is supposedly significant to the unification and development of a nation. This is especially so, as some studies have shown, where the shift of power to local government has created a series of hierarchically ordered units of administration at some of the lowest levels of government. The implication is a movement of power from the centre and may determine the scope of decentralization, nonetheless it involves a transition process that ultimately may change the characteristics of power structure of the different levels of government.